Mental Health Status and its Associated Factors among Students in Nawalparasi - Radhika Upadhyaya; Janaki Rai; Muna Sharma; Durga Prasad Pahari (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
Mental illness in children is very common in Nepal. It causes significant number of adolescents to deprive from education because of school dropout. This study aims to assess the mental health status and its associated factors among high school students at Devchuli Municipality, Nawalparasi. The study was cross-sectional and designed based on probability cluster sampling technique. The data was collected using self-administered General Health Questionnaire (GHQ-12). Mental health status was measured as psychiatric caseness using Goldberg criteria for GHQ 12 with cut-off point of three. Among 400 students, 387 students were participated in this study (97% participation rate), and the average age of the respondents was 17±1.58years with 31.3% prevalence of psychiatric caseness. Loneliness (AOR= 4.216 CI=1.395-12.739), sleeping less than 6 hours (AOR=3.720 CI=1.916-7.221), school absenteeism (AOR=3.562 CI=1.511-8.397), self-reported poor academic performance (AOR=2.459 CI=1.469-4.118), and inadequate perceived coping in stressful events (AOR=2.990 CI=1.430-6.252) were found to be significant factors affecting the psychiatric caseness among high school students. Based on our study, results suggest that one third of high school students were found as caseness and associated factors were loneliness, sleeping less than 6 hours in a day, school absenteeism, self-reported poor academic performance and perceived coping capacity. The findings suggest there should be provisional of social and psychological support in order to improve the quality of their life.